A multicriteria model for selecting eligible buyers for land consolidation - Scarelli, Antonino; Venzi, Lorenzo (International Journal of Strategic Property Management, 2004)
The problem of land consolidation is very relevant and Agricultural Policy has ruled particular conditions in the sales of farms. The adjacent neighbours must be involved (pre‐emption right) and in the case of more than one available for the stated price, the choice of the candidate having priority is not an easy task. It has, then, to be considered not only the subjective ability of the farmer, but also the nature, productivity, endowments of his farm with respect to the adjacent one in sale. The adopted procedure takes into account all the attributes related to the farm on sale, to the prospective buyers and their farms. The acquired information are evaluated by an entropy decisional process. The best solution is gained with respect to an ideal point, representing the perfect decision and having minimum entropy.First Published online: 18 Oct 2010